2016
DOI: 10.2459/jcm.0000000000000154
|View full text |Cite
|
Sign up to set email alerts
|

Axillary vein technique for pacemaker and implantable defibrillator leads implantation

Abstract: Different methods for venous access are used for permanent pacemaker or implantable cardioverter defibrillator (ICD), of which subclavian vein puncture technique is the most widely practised. Although this approach is relatively easy to learn, quick and offers high success rates, it may be associated with potential serious acute complications including pneumothorax, emopneumothorax, brachial plexus injury and longer-term complications such as lead fracture, loss of lead insulation and subclavian crush syndrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 21 publications
0
36
0
Order By: Relevance
“…The difference may be explained by the different study population (in our study all patients underwent ICD implantation) and the presence of severe vein spasm in two patients not reported by Antonelli et al We observed that the main cause (4.9 %) of failure was an abnormal course consisting of the vein not crossing the lateral edge of the first rib. Instead, the use of body surface of the second rib as landmark offered a significantly higher (100 %) success rate and a more lateral approach avoiding potential lead entrapment between the clavicle and the first rib, a cause of lead failure during follow-up [10]. Recently, Krahn, in a retrospective case-control study of 133 patients with Fidelis lead fractures, found that a more lateral vein access point is associated with a lower fracture risk [27].…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…The difference may be explained by the different study population (in our study all patients underwent ICD implantation) and the presence of severe vein spasm in two patients not reported by Antonelli et al We observed that the main cause (4.9 %) of failure was an abnormal course consisting of the vein not crossing the lateral edge of the first rib. Instead, the use of body surface of the second rib as landmark offered a significantly higher (100 %) success rate and a more lateral approach avoiding potential lead entrapment between the clavicle and the first rib, a cause of lead failure during follow-up [10]. Recently, Krahn, in a retrospective case-control study of 133 patients with Fidelis lead fractures, found that a more lateral vein access point is associated with a lower fracture risk [27].…”
Section: Discussionmentioning
confidence: 94%
“…Subsequently, various different techniques of axillary vein approach have been proposed ranging from a blind percutaneous puncture to the use of different tools such as contrast venography and ultrasound [10,[21][22][23][24][25][26]. Belott [23] described a technique for blind axillary vein puncture using anatomic landmarks by placing the needle tip fluoroscopically over the middle of the first rib prior to needle advancement through the pectoralis major muscle and maintaining this position by adjusting to a steeper needle angle when advancing to touch the rib.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The axillary vein is a common venous access point for placing a pacemaker or ICD lead during implantation of cardiac electronic devices and was first suggested by Byrd et al . Since then, various techniques have been recommended, ranging from venous puncture to use of several instruments, such as contrast venography or ultrasound . This approach has been preferred by many authors over the classical subclavian vein approach due to the possible reduced risk of pneumothorax and late lead fracture compared to subclavian vein access …”
Section: Discussionmentioning
confidence: 99%